(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Several scale insects species are recorded in Georgian vineyards. Among them the mealybug, Planococcus ficus (Signoret), and the cottony scale, Neopulvinaria innumerabilis (Rathvon), are the most prevalent and serious pests in the dry eastern regions. In the humid regions of the Black Sea coast the mealybug Pseudococcus vibumi (Signoret) is an occasional noxious pest. Other common coccids, Parthenolecanium corni (Bouche), P. persicae (F.), and Pulvinaria betulae L., are rare, minor pests in the vineyards and have no economic importance. Two hymenopterous s pecies, Anagyrus pseudococci (Girault) (Chalcidoidea, Encyrtidae) and Allotropa mecrida (Walker) (Proctotrupoidea, Platygasteridae), are parasitoids of P. ficus. Some species of hyperparasitoids have also been recorded, namely Pachyneuron muscarum (L.), Chartocerus subaeneus (Forster) and Marietta. picta (Andre). Currently, the key pest of vine in eastern Georgia is the cottony maple scale, where many outbreaks have occurred. Tb.is species of American origin (Canada, USA), spread in the Caucasus (Georgia, Armenia) and in some European countries (ijrance, Italy) without the natural enemies that suppressed it in America. No effective natural enemies have been found in Georgia. Three chalcid parasitoids, known as parasitoids of local coccids, have been recorded on this pest: Coccophagus maculipennis Jasnosh (whose natural host is Acanthopulvinaria orientalis (Nassonov)), C. palaeolecanii Jasnosh, and C. lycimnia Walker. The larvae of Leucopis alriceps (Czerny) (Diptera), Chrysopa spp. (Neuroptera) and Scymnus spp. (Coleoptera, Coccinellidae) have been recorded as predators. Breeding programs were initiated more than 50 years ago for tbe i1in-oduced coccu1ellid predator, C1yptolaemus montrouzieri Mulsant, to conu·oJ coccids. In regions with drier climates, where C. montrouzieri is less effective, a C. monrrouzieri strain introduced from Israel is being tested and preliminary experiments have found it to be more effective. In conclusion, indigenous natural enemies are not capable of reducing the impact of P. ficus and N. innumerabilis populations to non-economic levels. Developing effective biocontrol of these pests will be essential.